Rash and edema shortly after initial exposure to low dose cenobamate - Christopher Saouda; Yamane Makke; Helen Edelberg; Mohamad Z. Koubeissi (Epilepsy & Behavior Reports, 2025)
Cenobamate (CNB) is an antiseizure medication (ASM) approved for the treatment of focal epilepsy. Rash and edema are uncommon adverse effects of this medication. We report two patients with medically refractory epilepsy (MRE) who received CNB and developed chest and facial rash and edema after the initial dose of 12.5 mg/d that prompted discontinuation of the medication with ensuing resolution of the rash and edema. Rechallenging with CNB resulted in similar reactions. Our report aims at increasing awareness of these reactions to CNB.